AN ANALYSIS OF TABOO WORDS IN DEADPOOL MOVIE - RIRIN ZEVANYA PURBA; ZAINUDDIN ZAINUDDIN; I WY DIRGEYASA (LINGUISTICA, 2021)
The research dealt with taboo words in Deapool movie. The objectives of research aimed at explaining the types of taboo words and also to figure out motives of using taboo words in Deadpool movie. The research conducted by using descriptive qualitative method. This study was different from previous researcher that found types and function of taboo words while in this study focused on types and motives of using taboo words. The data were taken from the utterances that contain taboo words by first main character in this movie. There were 82 taboo words that had been uttered in this movie. From nine types of taboo words, there were eight of them, they were Cursing 2,44 %, Profanity 3,66 %, Obscenity 40,24%, Vulgarity 6,10 %, Insults and slurs 9,76 %, Slang 12,20 %, Epithets 20,73 %, and Scatology 2,44 %. And for the motives of using taboo words, there were five from five motives of them, they were Angry or Frustration 30,48 %, Descriptive- evaluative 43,90 %, Joking 7,32 %, Surprise 14,64 %, and Sarcastic Irony Insults 3,66 %.